Dental Caries - Zabokova Bilbilova, Efka (IntechOpen, 2021)
Dental caries are of vital concern to all dentists. Their management is central to daily work in dental offices because cavities are ubiquitous in all populations, lesion development is lifelong, and caries are the most common cause of tooth loss. This book provides information on the etiology, prevention, and treatment of tooth decay. Chapters cover such topics as dental biofilms, dietary factors, the association of Candida with early colonization of cariogenic microorganisms, oral diseases, the use of fluoride, and dental caries in disabled children. The information presented herein is useful for dental students as well as researchers and dental practitioners.